Quantifying transient interactions between amide groups and the guanidinium cation. Issue 43 (13th October 2015) - Balos, V.; Bonn, M.; Hunger, J.
Abstract : The guanidinium cation interacts with amide groups, the interaction strength is – compared to other cations – only intermediate. Abstract : We study the interaction of the guanidinium cation, a widely used protein denaturant, with amide groups, the common structural motif of proteins. Our results provide evidence for direct contact between guanidinium and ∼2 amide groups, but the interaction is transient and weaker than for other cations with high charge-density.